Implementasi Peraturan Mahkamah Agung Republik Indonesia Nomor 5 Tahun 2014 Tentang Pidana Tambahan Uang Pengganti Dalam Tindak Pidana Korupsi - Taufik Yanuar Chandra; Indik Rusmono (Universitas Jayabaya, 2020)
This study aims to examine that the Corruption Eradication Act, there are difficulties or obstacles in knowing the amount of funds from the results of criminal acts of corruption. Therefore, the Supreme Court issued a guideline in the Supreme Court Regulation Number 5 of 2014 concerning Criminal Additional Substitution in the Case of Corruption Crime. The provisions of the Supreme Court Regulation are intended to complement the weaknesses and shortcomings of the provisions of Article 18 of Law Number 31 of 1999 jo. Law Number 20 of 2001 concerning Eradication of Corruption. This study uses normative data with primary and secondary law data sources. Data collection techniques in this study are observation, documentation and literature study. The data collected is analyzed qualitatively. Found that the execution of substitute money based on a decision that has legal force remains contained in Article 9 of the Republic of Indonesia Supreme Court Regulation Number 5 of 2014. The results of the auction of state booty, according to Article 9 of the Regulation of the Minister of Finance Number 03 / PMK.06 / 2011 governing the handling of state spoils, aregiven full power to the service office to deposit into the state treasury as Non-Tax State Revenue in the form of general acceptance of the Prosecutor’s Office within 3 (three) months and can be extended for a maximum of 1 (one) month